STRUKTUR ANATOMI SEBELAS JENIS KAYU DARI JAWA BARAT - Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 1990)
Anatomical   featuru    of  eleoen  wood  species from  West Java were examined  and compared  for identification   purposes.  The reaul'tll  show  that  each  wood  species ean be diBtinguished  one from  the other.  All fibers N'ptate  is one chanu:temtic features  of family   Bwwraceae.    Tile celll pterospermum    types  distinguished   Planchonia   valida Bl. from  others  Species.Lit.sea rmna Hook.  has oil cellB, one  of  characteristic  features  of  family  Lauraceae.